Adopting the Cultural Strategy: Key to Enhancing Public Service - Nurmillah, Nurmillah; Nurdin, Nani Harlinda; Zainal, Nining Haslinda; Fatimah, Siti (Jurnal Manajemen Pelayanan Publik, 2024)
Public service tends to be a basic right of citizens and an entry point for the government because it has become its obligation to prosper its citizens. For this reason, this study aims to describe the cultural strategy proposed by David Osborne in seeing the quality of public services in Polongbangkeng Selatan District, Takalar Regency in South Sulawesi Province through the approach of changing habits, touching feelings, and changing mindsets. This research uses a qualitative descriptive approach. Data were collected through interviews with several informants and field observations. To strengthen the argument this research also uses documentation studies sourced from books, articles, and journals relevant to the topic of this research. The results showed that the three approaches in the cultural strategy have not been implemented optimally. To improve the quality of public services in Polongbangkeng Selatan Sub-district; it is imperative to implement organizational culture strategies, stop unproductive habits, improve service attitudes that arouse awareness, and adopt innovation and technology. Thus, it is expected that public services can become more effective, and efficient, and provide better satisfaction to the community.